Mining, lung cancer and smoking. - Axelson, Olav; Sundell, Lennart (Scandinavian Journal of Work, Environment & Health, 1978)
Several studies have shown an increased lung cancer mortality among Swedish metal and iron ore miners, as probably caused by exposure to radon and its daughters. An earlier study of zinc-lead miners has been updated. The results show a 16-fold increase in lung cancer mortality. Surprisingly, nonsmokers were more apt to develop lung cancer than smokers, but the induction-latency time was about nine years shorter on the average for the smokers. An explanation for these findings might be that smoking increases the thickness of the mucus layer and therefore protects the bronchial epithelium from alpha radiation, but it also promotes the development of cancer once induced by the radiation.
Keywords: case-control desing; case-referent desing; lung cancer; mining; radon daughter exposure; smoking